1999
DOI: 10.1152/ajpheart.1999.276.1.h159
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial defect mediates attenuated vasorelaxant response to isoproterenol after lung transplantation

Abstract: We have previously demonstrated that pulmonary vasodilation in response to isoproterenol is attenuated in conscious dogs after left lung autotransplantation (LLA). Our present goal was to identify the cellular mechanism responsible for this dysfunction. Size- and position-matched pulmonary arterial rings were isolated from the right (control) and left (LLA) lungs of 23 dogs 1–14 mo post-LLA. The rings were suspended for isometric tension recording and precontracted, and the vasorelaxant responses to activators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Our data showed that HG had no effect on production of cAMP stimulated by forskolin in rat small coronary arteries. Similar findings were reported by Yoshida et al (32), in which decreased dilation to isoproterenol was observed in pulmonary arteries with unchanged cAMP levels after lung transplantation where oxidative stress was enhanced. The direct effect of O 2 Ϫ ⅐, generated by hypoxanthine and xanthine oxidase, on cAMP and cGMP production was examined in cultured aortic smooth muscle cells from Wistar-Kyoto or spontaneously hypertensive rats (30).…”
Section: Discussionsupporting
confidence: 91%
“…Our data showed that HG had no effect on production of cAMP stimulated by forskolin in rat small coronary arteries. Similar findings were reported by Yoshida et al (32), in which decreased dilation to isoproterenol was observed in pulmonary arteries with unchanged cAMP levels after lung transplantation where oxidative stress was enhanced. The direct effect of O 2 Ϫ ⅐, generated by hypoxanthine and xanthine oxidase, on cAMP and cGMP production was examined in cultured aortic smooth muscle cells from Wistar-Kyoto or spontaneously hypertensive rats (30).…”
Section: Discussionsupporting
confidence: 91%
“…Isoprenaline increased the nitric oxide synthase and adenyl cyclase activity in human umbilical vein endothelial cells (Ferro et al ., 1999). Canine pulmonary arteries demonstrate endothelium dependent vasodilatation to isoprenaline via the release of NO leading to an increase in cyclic GMP in addition to an endothelium independent increase in cyclic AMP (Yoshida et al ., 1999). In adult rat pulmonary arteries it appears that ATP‐sensitive K + channels contribute to the isoprenaline induced relaxation of the smooth muscle cells (Sheridan et al ., 1997).…”
Section: Discussionmentioning
confidence: 99%